UNSUR BUDAYA JEPANG DALAM DONGENG MOMOTAROU - Fajria Noviana (Diponegoro University, 2017)
As one form of prose, fairy tale is a product of culture. As a product of culture, fairy tale consists ideas, norms, and many other from the community inside those fairy tales. As well as Japanese folktale Momotarou, it consists idea to live free from fear. Aside from the idea, this folktale also consists Japanese traditional culture and religious system. Therefore, this paper attempt to describe the result of research about Koentjaraningrat’s seven cultural elements in folktale Momotarou. Those seven cultural elements found in this folktale proof that its universal, and proof that religious system and social system is hard to be affected by another culture. These showed by Japanese people nowadays who still hold on to yaoyorozu no kami’s belief and bushidou.